Hak Privasi Era Digital: Konstitusi, Legislasi, Tantangan dan Hambatannya dalam Realitas Media Elektronik di Indonesia - Nathania Tessalonika Mingguw (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
One of the changes experienced by humans is communication technology. Along with the development of the era, communication technology has also developed massively until it reached the digital era like today. However, this development does not always have a positive impact. One of the negative impacts that arises is the violation of the right to privacy. The right to privacy that will be discussed is in the form of personal data. Legal problems related to personal data are one of them shown in the rampant buying and selling of personal data that occurred in Indonesia. The incident was suspected of being to attract the interest of marketing personnel. Through international instruments, the constitution, and its legislation, Indonesia has had a number of regulations related to the protection of the right to privacy in the form of personal data. However, of course, in its implementation there are still challenges and obstacles. The research method used in compiling this scientific article is the literature study method (normative juridical). Although Indonesia has many laws that regulate the protection of the right to privacy, regulations related to this matter have not yet fully succeeded in securing individual personal data properly.